2020
DOI: 10.1007/s00592-020-01506-8
|View full text |Cite|
|
Sign up to set email alerts
|

Fundamental principles of an effective diabetic retinopathy screening program

Abstract: Background Diabetic retinopathy (DR) is the leading cause of blindness among working-age adults worldwide. Early detection and treatment are necessary to forestall vision loss from DR. Methods A working group of ophthalmic and diabetes experts was established to develop a consensus on the key principles of an effective DR screening program. Recommendations are based on analysis of a structured literature review. Results The recommendations for implementing an effective DR screening program are: (1) Examination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 93 publications
0
29
0
Order By: Relevance
“…Determining the position of hard exudates can be a part of the diabetic macular oedema prediction algorithm. However, screening for diabetic macular oedema alone is currently not advised 33 . The essential parts of diabetic macular oedema examination and follow-up are fluoroangiography and ocular computer tomography examinations 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Determining the position of hard exudates can be a part of the diabetic macular oedema prediction algorithm. However, screening for diabetic macular oedema alone is currently not advised 33 . The essential parts of diabetic macular oedema examination and follow-up are fluoroangiography and ocular computer tomography examinations 34 .…”
Section: Discussionmentioning
confidence: 99%
“…The fundus photography was conducted by a trained specialist using a nonmydriatic fundus camera (TRC‐NW400, Topcon, Tokyo, Japan). For each eye, two images were obtained at 45° centered on the macula and optic papilla, which are suggested to be sufficient and superior to seven‐field imaging for effective DR screening, established by ophthalmic and diabetes experts 38 . The diagnosis and grading of DR were carried out by two trained specialists following the criteria of the Early Treatment of Diabetic Retinopathy Study 39 modified according to the clinical practice.…”
Section: Methodsmentioning
confidence: 99%
“…Inflammation/immune response and neurodegeneration processes are common pathogenic mechanisms associated with the most prevalent ocular diseases [1][2][3][4][5][6] The cellular and molecular mechanisms underlying these shifts display interesting similarities.…”
Section: State Of the Artmentioning
confidence: 99%
“…It has been recently reported that most challenging ocular disorders are uncorrected/under-corrected refractive errors, ocular surface dysfunction (OSD)/dry eye disease (DED), cataracts, glaucoma, diabetic retinopathy (DR) and age-related macular degeneration (AMD). In fact, severe visual impairment and blindness due to cataract or refractive error constitutes half of all global cases, being glaucoma the most common cause of irreversible blindness [1-3], with DR as the first cause of visual disability in working-age adults [1][2][3][4] and the AMD constituting the first cause of blindness in the elderly [1][2][3][4][5]. Overall, the above disorders seriously impair the quality of life related to vision.…”
Section: Introductionmentioning
confidence: 99%